Implementasi Data Mining Menggunakan Metode Deskripsi Untuk Mengetahui Pola Penentuan Penerima Bantuan Siswa Berprestasi - Piki Ashari Pasaribu (Bulletin of Information System Research, 2024)
Student achievement assistance is one of the programs run at MAN 2 Tapteng to support and motivate its students to continue to excel in academics. However, so far the determination of recipients of student achievement assistance at MAN 2 Tapteng still uses a manual method so that it takes a long time and process so that it is less effective. For that, the author conducted research and created a program to determine the pattern of determining recipients of student achievement assistance at MAN 2 Tapteng to be more efficient. The determination of the pattern of recipients of student achievement assistance is carried out by utilizing student report card data at the end of each semester. The method that is appropriate to this problem is the Description Method. Description is one of the functions in data mining to explore and collect a lot of data. The description method aims to explain or describe a situation, event and object. The results of this study are in the form of a pattern of determining recipients of student achievement assistance from each class at MAN 2 Tapteng. This program is expected to be more efficient in determining the pattern of recipients of student achievement assistance at MAN 2 Tapteng.